In-situ formed thermosensitive hydrogel amplifies statin-mediated immune checkpoint blockade for coordinated tumor chemo-immunotherapy - Liu, Zefan; Zhang, Yajun; Huang, Jinyu; Wang, Yan; Kang, Xin (Frontiers in Pharmacology, 2023)
Small molecule drugs are the next-generation of immune checkpoint inhibitors (ICIs), but their in vivo therapeutic outcomes remain unsatisfactory for a long time. Herein, we proposed a combinatory regimen that delivered a small molecule ICI and an immunogenic cell death inducer in an in-situ formed hydrogel scaffold based on thermosensitive materials (Pluronic F127). This platform increased the tumor retention of administrated small molecules, creating more opportunities for the interaction between drugs and tumor cells. We found that atorvastatin (ATO) effectively downregulated the expression of programmed death ligand 1 (PD-L1) and reversed compensative PD-L1 upregulation after cyclophosphamide (CTX) chemotherapy on CT26 colon tumors. CTX not only killed tumor cells to reduce the tumor burden, but also release damage-associated molecular patterns (DAMPs) to stimulate T cell immunity, therefore amplifying statin-mediated immunotherapy. The platform reported in this study might be promising to overcome the limitation of small molecule ICIs with short retention time and potentiate tumor chemo-immunotherapy.